Internet Access Equity Policy Is the Internet Access Equity Policy Through USO Funds effective? - Rossi Adi Nugroho; Binti Azizatun Nafi'ah (IJID (International Journal on Informatics for Development), 2019)
Indonesia has a disparity in internet access caused by differences in regional factors, especially in geographically difficult areas to reach. The disparity in internet access is narrowed by the existence of programs through USO funds. However, the researchers found that the equalization program for internet access using USO funds had not been effective, especially in the education sector. This paper aims to provide an evaluation of USO-funded programs. This paper uses qualitative descriptive methods with review literature data collection techniques accompanied by qualitative critical analysis techniques. The important finding of this study is that the internet access equalization program has not been effective as evidenced by the ineffectiveness of this program in the education sector. Researchers suggest optimizing the internet access equalization program through USO funds to improve the quality of education.